Body posture, postural stability and body composition in goalkeepers of the polish national junior handball team - Wilczynski, J.; Dutkiewicz, R.; Wilczynski, I. (Journal of Kinesiology and Exercise Sciences, 2016)
Aim. The objective of the study was to evaluate body posture, postural stability as well as body composition and to analyze the relationship between these parameters in goalkeepers of the Polish National Junior Handball Team. Basic procedures. The study covered 11 goalkeepers of the Polish National Junior Handball Team, aged 15-19. Body posture was evaluated by the Diers Formetric III 4D optoelectronic method. Postural stability was examined using the Biodex Balance System platform. The study was conducted in the Posturology Laboratory at the Institute of Physiotherapy at the Faculty of Medicine and Medical Sciences, UJK in Kielce. Results Main findings. The flattening of the thoracic kyphotic angle and lumbar lordotic angle was observed. The majority of adolescents in the study had residual scoliosis (12.36°). During the Postural Stability Test, all of them remained in Zone A (the best stability), and in the majority of cases had a tendency towards sway to the right posterior (% Time In Quadrant I). A positive correlation was found between the trunk length from vertebra C7 to the central point between the sacral dimples (r=0.6507; p=0.030) and the trunk length VP-SP from C7 to the beginning of the groove between the buttocks, and the percentage of staying in Quadrant 1 (% Time In Quadrant I), i.e. sway to the right anterior (r=0.6317; p=0.037). Conclusions. Handball is a discipline of sports discipline asymmetric in nature, which may be the cause of the occurrence of posture defects. Postural education exercises should be included in the training programme of juniors.